2004
DOI: 10.1097/00005176-200411000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Glycol 3350 Without Electrolytes for the Treatment of Functional Constipation in Infants and Toddlers

Abstract: PEG is effective, well tolerated and appeared safe for the treatment of functional constipation in children <2 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 12 publications
5
39
0
6
Order By: Relevance
“…Mais recentemente, o polietilenoglicol (PEG) vem sendo citado como opção terapêutica [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] na CICF em pediatria.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Mais recentemente, o polietilenoglicol (PEG) vem sendo citado como opção terapêutica [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] na CICF em pediatria.…”
Section: Introductionunclassified
“…O PEG sem eletrólitos diferencia-se dos outros laxativos utilizados por ser insípido e inodoro 16,19,[23][24][25][26] .…”
Section: Introductionunclassified
“…O sabor e o volume em que são empregados contribuem para uma menor adesão (5,36) . O PEG é inodoro, insípido e pouco absorvido pelo organismo (<0,1%) (20,22,24,25,27,31,32,34,36) . Exerce uma ação osmótica, não irritativa, com consequente aumento do conteúdo de água das fezes, sem ser degradado pelas bactérias intestinais (21,23,25,27,36) .…”
Section: Revisãounclassified
“…O PEG é inodoro, insípido e pouco absorvido pelo organismo (<0,1%) (20,22,24,25,27,31,32,34,36) . Exerce uma ação osmótica, não irritativa, com consequente aumento do conteúdo de água das fezes, sem ser degradado pelas bactérias intestinais (21,23,25,27,36) . Apresentado em forma de pó, em saches, com dose individualizada, tem a vantagem de poder ser misturado a vários tipos de líquidos (água, sucos e leite) (21,25,31,36,39) .…”
Section: Revisãounclassified
“…In the last decade, polyethylene glycol (PEG) 3350 has been introduced to children and was found to be palatable and acceptable by children for the treatment of various medical conditions, mainly constipation. Several studies have shown that children will accept this PEG based solution and the compli-ance rate was very good even for long term therapy [4][5][6][7] . In the past, we showed that PEG 3350 is an excellent solution for colon cleansing protocol in children reaching adequate colon preparation in up to 92% of the children examined [8] .…”
Section: Introductionmentioning
confidence: 99%